Blunt Abdominal Trauma in Geriatric Populations in a RuralNigerian Community: Clinical Outcomes, SocioeconomicBarriers, and Systemic Challenges (Western Journal of Medical and Biomedical Sciences, 2025)
Geriatric populations in rural Nigeria face disproportionately high risks from blunt abdominal trauma (BAT) due to physiological fragility, limited healthcare access, and socioeconomic marginalization. This retrospective cohort study analyzed 32 patients aged >65 years admitted with BAT at Alex Ekwueme Federal University Teaching Hospital (AEFUTHA), Abakaliki, a referral center for southeastern Nigeria's agrarian communities, where geriatric patients accounted for 32.1% of all BAT cases over a two-year period (2022–2023). Data on demographics, injury mechanisms, clinical management, and outcomes were extracted from hospital records and analyzed using SPSS v28. The cohort (median age: 73 years, IQR: 68–79) was predominantly male (65.6%, n=21) and engaged in subsistence farming (81.3%, n=26). Falls (40.6%, n=13), assaults (25.0%, n=8), and road crashes (18.8%, n=6) were the primary injury mechanisms. Delayed hospital presentation (>24 hours) occurred in 84.4% (n=27) of cases, with 53.1% (n=17) initially seeking traditional healers. Clinically, 68.8% (n=22) presented with baseline anemia (Hb
Keywords: Blunt abdominal trauma; Catastrophic health expenditure; Geriatric trauma; Health equity; Rural Nigeria; Sepsis; Surgical delays